2008
DOI: 10.1097/sle.0b013e318155abd1
|View full text |Cite
|
Sign up to set email alerts
|

The “Double Endoloop” Technique—A Simple Alternative Technique for Laparoscopic Appendectomy

Abstract: Diagnostic laparoscopy is now being frequently used in the emergency management of patients with acute lower abdominal pain, particularly where appendicitis is suspected. It is particularly useful in women where other responsible gynecologic causes can be diagnosed and treated thereby decreasing the rate of negative open appendectomy. Recent advances in laparoscopic techniques have resulted in increasing numbers of patients proceeding to laparoscopic appendectomy. Here, we describe a modification of laparoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Despite the fact that many authors have described several modifications with new materials for appendiceal stump closure, an optimal closure material has not yet been determined. [7][8][9][10][11][12][13][14][15][16] Moreover, most of these materials may prolong the operation time or increase cost, which may limit the popularity of laparoscopic appendectomy. 6,8,9,21 Recently, linear staplers and endoloops, both equally safe, have frequently been used as an alternative in the closure of the appendiceal stump during laparoscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that many authors have described several modifications with new materials for appendiceal stump closure, an optimal closure material has not yet been determined. [7][8][9][10][11][12][13][14][15][16] Moreover, most of these materials may prolong the operation time or increase cost, which may limit the popularity of laparoscopic appendectomy. 6,8,9,21 Recently, linear staplers and endoloops, both equally safe, have frequently been used as an alternative in the closure of the appendiceal stump during laparoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, several modifications to the original technique with new materials have been introduced for optimizing and controlling the appendiceal stump closure, such as the endoloop, double endoloop, ultrasonically activated scalpel, instrument-assisted knotting, bipolar coagulation, slip-knot tying, metal clip, hem-o-lok polymeric clip, and linear endostaplers. [6][7][8][9][10][11][12][13][14] Controversies about the efficacy and safety of these novel materials still exist, [7][8][9][10][11][12][13][14][15][16] and the need to evaluate the various technical aspects of these novel materials through new research has become ever more important. In our institute, it is routine practice to use intracorporeal polyglactin knot-tying sutures for appendiceal stump closure during laparoscopic appendectomy.…”
mentioning
confidence: 99%
“…There was no significant difference in mean age at operation (EL: 9.1 years [range, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested that there is an increased risk for postoperative complications, such as intra‐abdominal abscess formation and small bowel obstruction, in complicated appendicitis, both in children and adults (4,6). Complicated appendicitis is associated with more inflammation than uncomplicated appendicitis, and it is generally believed that when the mesoappendix and the base of the appendix are fragile by perforation or gangrene, EL is unsuitable (7). In addition, higher incidences of leakage and intra‐abdominal abscess formation have been reported after LA using EL compared with ES, especially in complicated appendicitis (3); this is related partly to the condition of the mucosa of the appendiceal stump, which is everted with EL and inverted with ES (8).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many methods have been recommended and examined for its closure, some of these methods include endoloop, double endoloop, cutting with ultrasonic knife, tying with instrument, metal or plyometric clips, ligator and thread, hemolock, and linear endostapler. [567] Linear stapler and endoloop are nowadays often used as alternatives for closing appendiceal stump in laparoscopic appendectomy since they are equally safe. [568] Regarding each of these methods, the matter of being economic must also be considered in addition to the issue of safety.…”
Section: Introductionmentioning
confidence: 99%